ZAZNAVANJE IN POJMI: TEMELJI REALISTIČNE ESTETIKE (Filološke pripombe, 2019)
The discussion concerning the relation between perception and concepts concerns the basis of each realist aesthetics. There is a fact though that such a relation tends to be misunderstood because of deep presuppositions that are proper to our cognitive apparatus. Therefore a beginning hint in respect to the real ontological nature of the world is needed: in the sense of the parmenidean materialism the world is understood as one world. This unity is compatible with dynamics, because continuity is the effect of dynamics.